The role of defects, deuterium, and surface morphology on the optical response of beryllium. (1st May 2022) - Minissale, M.; Louis De Canonville, C.; Pardanaud, C.; Butoi, B.; Bisson, R.; Gallais, L.
Abstract: The knowledge of optical properties of beryllium is of crucial importance in fields such as nuclear fusion and aerospace applications. The optical properties of pure beryllium are known in the visible and infrared domains. Nevertheless, the role of different physico-chemical parameters such as composition and surface roughness, that is often neglected in first approximation, deserves dedicated comprehensive studies. In this work we have studied the optical properties of bulk beryllium and magnetron sputtering beryllium layers in the 500–2000 nm spectral range. Experimental measurements show that beryllium reflectivity strongly depends both on bulk fabrication procedure and on surface preparation. Different models allow us to perform a quantitative interpretation of reflectivity results and to study the influence of different parameters: (i) a multi-reflection interference model to understand the role of oxide layer, (ii) a Lorentz–Drude model for the bulk composition effect, (iii) scattering models for the surface roughness, and (iv) the Maxwell–Garnett model for the surface porosity. The calculated relative permittivity of the studied samples is used to evaluate the emissivity in the visible and infrared domain. Such evaluation, giving indications of possible evolution of optical properties of beryllium in a plasma environment, can provide a useful tool for thermography studies of tokamak walls.